Dialogue against the Jews - Petrus Alfonsi, 1062-1110? (Book collections on Project MUSE., 2006)
"Petrus Alfonsi's Dialogue Against the Jews (ca. 1109) breaks new ground in the history of Christian anti-Jewish polemics. As a recent convert from Judaism, Alfonsi introduced an intimate knowledge of Jewish literature and contemporary practice absent from earlier Christian sources. This knowledge enabled him to attack for the first time the Talmud (or, more broadly, post-biblical Jewish literature) as a source of Jewish error, with arguments drawn from philosophy and theology, astronomy, medicine, and physics. Equally important, Alfonsi's Dialogue contains an extensive anti-Muslim polemic to explain not only why he abandoned Judaism but also why he rejected Islam and chose the Christian faith." "Never before translated into English, this work presents to the reader perhaps the most important source for an intensifying medieval Christian-Jewish debate."--Jacket